(untitled) (Baltic Journal of Sport and Health Sciences, 2021)
Background. Athlete brand image management is one of the most popular topics of discussion in sport management right now. As professional sport has become a commercialised industry segment with more athletes involved, athletes are becoming promotional faces. Most professional athletes are involved in the use of social networks. There athletes actively demonstrate their personal lives, professional accents and advertise products. It is important to understand and analyse the impact of social networks on an athlete’s brand and ways to properly position themselves in social media. Using social networks, athletes are closer to fans and consumers than ever before. Based on and applying the Athlete Brand model developed by Arai (2010), this study aimed to investigate students’ attitudes towards athletes’ self-positioning on social networks. Methods. The study involved 367 students (151 men and 216 women) from three Lithuanian universities. The Arai (2010) questionnaire was used for the study. Statistical analysis of the data was performed using SPSS 26.0. Results. It has been found that athletes’ sports performance is statistically significant in the development of a professional athlete’s brand, it is the fundamental aspect that creates the initial status of athlete’s brand. Results showed that the strongest direct causal link was found between an athlete’s athletic performance and lifestyle. It was also found that very strong links, in the opinion of the respondents, were between the athletes’ communication and behaviours. Conclusions. When building an athlete’s brand, it is important to pay attention to three key components: athletic performance, attractive appearance, and marketable lifestyle. These three uses of an athlete’s brand can be explained by specific aspects of sports competitions or components of personal life. However, one of the most important factors in shaping a positive image of an athlete is athletic achievements. Practical implications. This study can provide a consistent consumer approach to key aspects, focusing on consumer attention in athlete positioning. This can help the athlete and marketers develop an appropriate personal branding and positioning strategy in social media, which will then broaden the circle of fans and strengthen the opinion of loyal fans. Athlete’s brand is a set of closely interrelated and fan-centred physical, functional, aesthetic, and emotional elements that sets athlete’s brand apart from competitors and creates financial benefits for the athlete. The brand creates benefits not only for the athlete, but also for the market participants around him/her (consumer/fan, commercial brand), which can be called the functions of the brand. Keywords: Athlete’s image, social network, brand relationship.